The case of (per) addietro in Old Florentine. When before was (apparently) based on back - Franco, Ludovico (Onomázein, 2015)
The aim of this paper is to describe what prima facie seems to be a typological rarum in Old Florentine (i.e. Old Italian). Specifically, we address here the morphosyntax of the temporal adverbial (per) addietro (lit. for at-back), which was commonly used in Old Florentine texts to encode a meaning roughly corresponding to [BEFORE]. Thus, it seems to go against the accepted generalization that spatial relations of front and back regularly express, respectively, anteriority and posteriority across languages when they are ‘shifted’ from space to time (Haspelmath, 1997). We will provide a simple morphosyntactic explanation of the seemingly ‘exceptionality’ of (per) addietro based on a finer-grained representation of temporal expressions and a locality constraint on hierarchical structure triggering kinda-suppletive patterns (Bobaljik, 2012; Moskal, 2013).